Pre-surgery inflammatory and angiogenesis biomarkers as predictors of 12-month cancer-related distress: results from the ColoCare study - Lindley, Clara; Gigić, Biljana; Peoples, Anita R.; Han, Claire J.; Lin, Tengda; Himbert, Caroline; Warby, Christy A.; Boehm, Juergen; Hardikar, Sheetal; Ashworth, Anjelica; Schneider, Martin; Ulrich, Alexis; et al. (Cancer epidemiology, biomarkers & prevention, 2023)
Patients with colorectal cancer commonly suffer from complex psychological distress. Elevated distress may be linked to systemic biomarkers. We investigated associations of biomarkers of inflammation and angiogenesis with cancerrelated distress (CTXD) score.
Online veröffentlicht am 6. März 2023
Gesehen am 30.11.2023